WOMEN'S ROLE IN JOHN LEE HANCOCKS THE BLIND SIDE (2009) MOVIE : A FEMINIST PERSPECTIVE - MUNTO VIA N, RAHMA (2011)
This study is aimed to show the women role in The Blind Side movie by using feminist perspective. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the feminist perspective. The researcher employs the descriptive qualitative research as a type of the research. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the movie and script of The Blind Side movie and the secondary data source is information related to the primary data source, website, and book about feminist perspective. The method of collecting data is observation and library review. The method of analyzing data is descriptive technique. Having analyzed this film, the writer draws some conclusions as follows. Firstly, based on the structural analysis of each elements, it shows that the character and characterization, plot, setting, point of view, theme, mise en scene, cinematography, sound, and editing are related to each other and form unity to be good quality of a movie . Secondly, Jhon Lee Hancock wants to say that someone's success cann't be separated from women's role. The last, based feminist perspective the author wants assert that everyone has to realize the important of women's role in family, career and society.